2017
DOI: 10.3389/fpls.2017.00577
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Map of Mango: A Tool for Mango Breeding

Abstract: Mango (Mangifera indica) is an economically and nutritionally important tropical/subtropical tree fruit crop. Most of the current commercial cultivars are selections rather than the products of breeding programs. To improve the efficiency of mango breeding, molecular markers have been used to create a consensus genetic map that identifies all 20 linkage groups in seven mapping populations. Polyembryony is an important mango trait, used for clonal propagation of cultivars and rootstocks. In polyembryonic mango … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 31 publications
0
57
0
5
Order By: Relevance
“…However, the subsequent genetic evidence proved that poly-embryony in mango is actually under the control of a single dominant locus. A study conducted by Kuhn et al (2017) reported a significant association between a single locus with the dimorphic seed type (mono-embryonic and poly-embryonic) in Linkage Group 8 (LG8). Their study also suggested that a heterozygous dominant allele regulates polyembryony, while the homozygous recessive allele regulates monoembryony.…”
Section: Discussionmentioning
confidence: 99%
“…However, the subsequent genetic evidence proved that poly-embryony in mango is actually under the control of a single dominant locus. A study conducted by Kuhn et al (2017) reported a significant association between a single locus with the dimorphic seed type (mono-embryonic and poly-embryonic) in Linkage Group 8 (LG8). Their study also suggested that a heterozygous dominant allele regulates polyembryony, while the homozygous recessive allele regulates monoembryony.…”
Section: Discussionmentioning
confidence: 99%
“…The generation of a large number of mango varieties have progressively speeded its wide-reaching distribution in the world 7 . Although some cytogenetics data 8 , genetic mapping 9,10 and transcriptomics data 11,12 are publicly available, the lack of chromosome-level high-quality mango reference genome sequences has seriously hampered our understanding of the genetic basis of specialized phytochemical composites and allele mining in genomics-assisted breeding for mango improvement.…”
Section: Background and Summarymentioning
confidence: 99%
“…Despite the availability of cytogenetics data [9], transcriptome data [10,11], and genetic maps [12,13], whole-genome resources for mangoes are still publically unavailable, which creates difficulties in genomic-based trait improvement and understanding of specialized Anacardiaceae biochemistry underneath. To conquer this, we sequenced and assembled the chromosome-level genome of mangoes.…”
Section: Introductionmentioning
confidence: 99%